FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT LEVERAGE (Students' Journal of Economic and Management, 2013)
This study examines the effect of assets structure, growth, profitability, risk and firm size to leverage in manufacture companies. The population of this research is 140 manufacture company which its listed in Indonesian Stock Exchange period 2008-2010. Sampling technique used here is purposive sampling on criterian the company that listed in Indonesian Stock Exchange 2008-2010 and represent their finacial report period 2003-2010, continually have debts during period 2008-2010, continually have operating income during period 2003-2010, and continually have operating income before tax during period 2008-2010. The data is obtained based on Indonesian Capital Market Directory (ICMD) period report 2003-2010. It is gained sample amount of 57 companies. The analysis technique used here is multiple regression with the least square difference and hypothesis test usingt-stastitic to examine partial regression coefficient and F-statistic to examine the mean of mutual effect with level of significane 5 %. This research result that assets structure, growth, and risk gives posititive not significant effect on leverage, while profitability gives negative significant to leverage. Firm size has negative not significant to leverage. Simultaneously assets structure, growth, profitability, risk and firm size proof significantly influent leverage in level less than 5 %.   Keywords : assets structure, growth, profitability, risk, firm size and leverage